Peculiarities of general cultural and political values transformation in Russia - B. S. Nevolin; V. F. Nitsevich (Управление)
The relevance of the study is due to the fact that over the past thirty years Russian state cultural policy has been focused on strengthening democratic cultural values, but in recent years the situation has begun to change dramatically. The ruling elite of the country announced the state cultural policy reorientation, which should now be based exclusively on traditional values. The purpose of the study is to identify features of the general cultural and political values system transformation in Russia. The objectives of the article are to identify current general cultural and political values that fall under the category of “traditional”, to establish value orientations that are most significant for Russians at present, and to determine degree of risk of a value split in Russian society. The research was conducted using such methods as classical document analysis, social survey, comparative analysis, systematization, and visualization methods. The results of the study show that the values accepted as traditional and the values identified by respondents as significant coincide in such positions as justice, human rights, freedom, patriotism, morality, collectivism, and mutual aid. No immediate threat of degradation of Russian society’s values has been identified. The risks associated with a possible split in society are moderate. The results of the sociological study allow us to conclude that the political views of one part of the Russian society are polarized, but the level of apolitical attitude of the other part is increasing.